Influence of the intelligence project at Harvard cognitive development of students in primary education. Implications for organizational and professional development in second and third cycle of primary education - Ramos Fresno, Mercedes (Avances en Supervisión Educativa, 2014)
This study aims to identify the influence of the Harvard Project on IQ Intelligence students of second and third cycle of primary education and the implications for the organizational and professional development of teachers . The experience has been developed over four courses in a public school in Madrid. The methodology used , complementary , included group designs with pretest-posttest measures , participant observation and interviews. The results show the positive impact of PIH on IQ and can say that the application of PIH produce cognitive improvements in students , as measured by the intelligence test "g" of Cattell . Regarding the implications for the organizational and professional development, we have found that the implementation of PIH promotes the development of teacher professional autonomy , commitment to teaching practice , and the necessary self-criticism to constantly evaluate , creating flexible educational proposals through self-reflection. The communication of this experience positively influences both the school community and the local community, encouraging them to participate in educational projects aimed at improving the quality of teaching- learning and education.